PERANAN CURB65 SEBAGAI PREDIKTOR KELUARAN PADA CEDERA KEPALA SEDANG BERAT SUATU STUDI PENDAHULUAN - Dharmawita, Mursyid Bustami, Ceva Wicaksono, Joedo Prihartono (NEURONA, 2013)
INTRODUCTION MODERATE AND SEVERE TRAUMATIC BRAIN INJURY TBI PATIENTS REQUIRE HOSPITALIZATION THEY HAVE HIGHER RISK IN DEVELOPING NOSOCOMIAL INFECTIONS SUCH AS PNEUMONIA WHICH CAN WORSEN THEIR OUTCOMES SINCE THERE ARE MANY FACTORS CAN AFFECT THE OUTCOME OF HEADINJURED PATIENTS WITH PNEUMONIA A SCORING SYSTEM FOR EVALUATING THE SEVERITY OF PNEUMONIA IS NEEDED CURB65 WAS A RECOMMENDED SCORING IN EUROPA AS ITS PRACTICAL TO USE BUT ITS NEVER BEING INVESTIGATED AS AN OUTCOME PREDICTOR IN HOSPITALISED TBI CASES